LOCAL METHODS OF TREATING ANEMIA IN WOMEN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores local and traditional approaches to treating anemia in women, especially in resource-limited and rural settings. By analyzing both cultural practices and scientific evaluations of natural remedies, the article aims to assess their effectiveness, benefits, and limitations. The article also integrates recent data and field studies to discuss how these methods may complement modern medical treatments.